A novel green approach for silver recovery from chloride leaching solutions through photodeposition on zinc oxide. (15th March 2023) - Muscetta, Marica; Clarizia, Laura; Race, Marco; Pirozzi, Francesco; Marotta, Raffaele; Andreozzi, Roberto; Di Somma, Ilaria
Abstract: Silver is extensively used in electronics, industrial catalysis, and biomedical sector owing to its enhanced physicochemical properties. E-waste recycling may contribute significantly to enhance silver recovery in the view of a circular economy and limit the depletion of mineral sources. In this scenario, hydrometallurgical routes represent the most widely used techniques for silver extraction/recovery and require strong acidic solutions, high temperatures, and multiple operating units. An alternative sustainable route for silver recovery from leaching solutions used for silver extraction in industrial applications is herein proposed for the first time. The novel green process of silver recovery is based on the UV/vis light-driven photocatalytic deposition of pure metallic silver over low-cost and non-toxic ZnO photocatalyst. In the second step, ZnO is dissolved by slight acidification and pure metallic silver is easily recovered. Low environmental impact, mild operating conditions, and economic viability are among the major perks of the new silver recovery process developed. In the view of a full-scale implementation, several operating conditions of the recovery process (i.e., photocatalyst load, starting silver concentration, type of hole scavenger and irradiation) were thoroughly investigated. A mathematical model capable of describing the system behaviour under different operating conditions was also developed and allowed to estimate unknown kinetic parameters for the Ag-photodeposition process. Graphical abstract: Image 1 Highlights: Green Ag recovery approach from leaching solutions replaces hydrometallurgical routes. Novel green process of Ag recovery via UV light-driven photodeposition of Ag over ZnO. ZnO photocatalyst dissolution and recovery thorough slight acidification. Low environmental and economic impact of the new silver recovery process developed. Mathematical model estimating unknown kinetic parameters of Ag photodeposition.